A Dropper Remover Tool - Muhammad, Muhammad Alif Hakim bin Mohd Shukri; Abdullah, Nurul Azma (Applied Information Technology And Computer Science, 2023)
All devices need protection to prevent any data being breach. Antivirus create specifically to help, prevent and remove malware. Dropper is one of malware that usually called payload because once it penetrates the system, it will release malware into it. To protect devices being attack by dropper, A Dropper Remover Tool developed. This tool could protect the devices from being attack by detecting and removing the dropper. Object-oriented analysis and design used to develop the tool. User can choose the file that user want to scan it. After that, user can scan the file that will indicates whether the file is clean or infected. If infected, user can remove the file. User also can list out all the file that contains in the selected folder. Development of this tool will protect the devices at least from dropper. The tool easily can be installed and use since it only available in Windows operating system. Besides, this tool can be improved by able to use in Linux and any operating system. This tool can add more features in future such as firewall, blocking website and so on to avoid user download free application in unsecure website.